Identification Liangan Site: Archeological Predictive Modeling - Anindya Puspita Putri (Technium Social Sciences Journal, 2023)
This research was conducted in Liangan Site, an archeological Hindu temple site situated on the eastern slope of Mt. Sundoro, Temanggung District. The discovery of Liangan Site was in the area of sand mining. This research’s interest is trying to disclose of the spatial component of the site that are important to the history, science and culture. The objectives of this research: Mapping the width of Liangan Site that still has the potential to contain of archaeological artifacts. The method that used for this research analyze the distribution of archaeological remains at the Liangan Site with the scoring method through field surveys. While cultural resource management is done by knowing the predictions of the length area of the site using Archaeological Predictive Modeling. Results from this research include the entire potential zone that contains archaeological remains at the site of 20,71 ha. The zone sensitivity archaeological remains are divided into zones of high sensitivity (3.007 ha), medium sensitivity zones (4.369 ha) and low sensitivity zones (13.34 ha).